2022
DOI: 10.3390/nu14040866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity Surgery on Taste

Abstract: Obesity surgery is a highly efficacious treatment for obesity and its comorbidities. The underlying mechanisms of weight loss after obesity surgery are not yet fully understood. Changes to taste function could be a contributing factor. However, the pattern of change in different taste domains and among obesity surgery operations is not consistent in the literature. A systematic search was performed to identify all articles investigating gustation in human studies following bariatric procedures. A total of 3323… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 121 publications
1
19
0
Order By: Relevance
“…However, the exact mechanisms by which SG induces weight loss are not completely clear. While there is a general agreement that the reduction in volume of food plays a central role in post-SG weight loss [ 34 ], some studies suggest that changes in what patients eat may also contribute [ 1 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the exact mechanisms by which SG induces weight loss are not completely clear. While there is a general agreement that the reduction in volume of food plays a central role in post-SG weight loss [ 34 ], some studies suggest that changes in what patients eat may also contribute [ 1 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was shown to lower gustatory sensitivity in both children and adults, and there are studies on the preference for sweet taste in patients with obesity [ 4 , 5 , 6 , 7 , 8 , 9 ]. In this regard, it has been suggested that patients after SG change their preference from high to lower caloric density food [ 1 , 15 , 16 , 17 ]. Based on our findings, we are able to support the evidence that changes in taste, desire, and enjoyment of taste are very common after SG, with a reduced preference for food with high sugar and fat content and an increased postoperative preference for low-sugar and -fat foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taste receptors (TRs) are found in oral and extra-oral sites, as well as in the digestive system, where they are localized in the epithelial cells, including the enteroendocrine (EEC) cells of the gastrointestinal (GI) mucosa lining, and play a critical role in integrating inputs from luminal content and regulating food intake through a gut–brain pathway [ 11 ]. Although taste is one of the most important factors influencing feeding behaviors, the number of studies on the gustatory sensitivity of obese patients is still scarce and heterogeneous [ 12 ]. Most of the studies have focused on the impaired taste sensitivity in obese subjects and on the change in sweet taste perception [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%